The optimal exploitation of sensory electrical stimulation for regulating postural balance depends on participants’ intrinsic balance abilities - Paillard, Thierry; Zéronian, Sacha; Noé, Frédéric (Journal of clinical neuroscience, 2021)
•Improving postural balance using somatosensory stimulation is not systematic.•Interindividual variability could explain the heterogeneous nature of the results.•Individuals with the worst initial balance control benefit more from stimulation. The sensory electrical stimulation applied to the postural muscles provides additional sensory information that improves postural balance but this improvement seems to be highly subject-dependent. The first aim was to analyse the effects of sensory electrical stimulation on postural balance and the second aim was to analyse these effects depending on intrinsic postural balance abilities of subjects. Twenty healthy young male participants completed a monopedal postural task with sensory electrical stimulation (1 ms; 10 Hz; 7 ± 2 mA i.e., twice the intensity corresponding to the sensory threshold) and without sensory electrical stimulation. Pearson’s product-moment correlations were performed on centre of pressure parameters to assess whether the participant’s balance abilities at baseline were related to the beneficial effects of sensory electrical stimulation. The results showed positive correlations for all the variables measured (i.e., with r2 from 0.32 to 0.35). Evidence suggests that subjects’ abilities to take advantage from electrically induced additional afferents depended on participants’ intrinsic balance abilities. In fact, subjects who exhibited the worst postural balance at baseline (i.e. without stimulation) benefited more from the effects of sensory electrical stimulation than subjects who displayed the best postural balance at baseline. In physically impaired subjects, as part of functional rehabilitation, sensory electrical stimulation would be particularly interesting in order to limit their risk of falling.